(untitled) - Shurtleff, William (New York, 1975)
An Incredible Food From The East To Revolutionize Cooking In The West. Amazingly versatile, ideal for weight control, low in saturated fats and cholesterol free, tofu is widely available in America today. This beautifully illustrated book is a complete guide to tofu, its forms, its traditions, including: 250 Gourmet Recipes from East and West -- Soups, Salads, Dressings, Sauces, Main Dishes, Casseroles, Barbecued and Deep-Fried Specialties, and Desserts Easy-to-Follow Instructions for Making 7 Varieties of Tofu at Home. The protein backbone of East Asian diets, tofu offers an ideal answer to the protein problem for millions of nutrition-conscious Americans. Natural and inexpensive, quick and easy to prepare, an inspiration to creative cookery, tofu is a miraculous addition to the American menu, a food of the future
Keywords: Food